Development of high copper concentration, low operating temperature, and environmentally friendly electroless copper plating using a copper ‐ glycerin complex solution. (1st September 2022) - Huang, J.H.; Shih, P.S.; Renganathan, V.; Grӓfner, S.J.; Chen, Y.A.; Huang, C.H.; Kao, C.L.; Lin, Y.S.; Hung, Y.C.; Kao, C.R.
Highlights: Temperature and copper sulfate concentration dominate high Cu concentration solution. Copper forms 1:2 complexes with glycerin. High Cu concentration solution has high uniformity on a small scale. Abstract: Few researchers have studied high metal ions concentration electroless plating solutions since increasing metal ions concentration shortens the solution life considerably. Nevertheless, as the required thickness of the electroless plating film reduces gradually, the limited solution life will not be a large problem. There are no detailed studies on the influence of high copper concentration electroless copper plating solution and their composition on the plating rate and decomposition time. Therefore, this paper explores the plating characteristics of high copper concentration from a copper‐glycerin complex solution. Taguchi's approach was used to optimize the plating rate and decomposition time based on an L18 orthogonal array with six main effect parameters and three levels. Main effect response tables and plots were employed to investigate the parameter influence. The significant factors of plating rate are temperature and pH, and the concentration of copper sulfate has much influence on the decomposition time. Temperature and copper sulfate concentration are the key factors to optimize the formulation of the plating solution. The optimized results were obtained at 0.18 M copper sulfate, 0.133 M formaldehyde, 0.36 M glycerin, 3.2 × 10 −5  M 2, 2'-dipyridyl, 29 °C, pH = 12.8. The copper concentration was more than four times higher than the conventional electroless copper plating solution, and the critical factors of high copper concentration in the electroless copper plating solution were revealed. It was found that copper formed 1:2 complexes with glycerin at a pH value of 12.8. In addition, the surface morphology and the uniformity of the plating layer were included as well.